Cranberry (poly)phenol metabolites correlate with improvements in vascular function: A double‐blind, randomized, controlled, dose‐response, crossover study. Issue 10 (16th June 2016) - Rodriguez‐Mateos, Ana; Feliciano, Rodrigo P; Boeres, Albert; Weber, Timon; dos Santos, Claudia Nunes; Ventura, M. Rita; Heiss, Christian
Abstract : Flow‐mediated dilation (FMD) was determined after consumption of cranberry juices containing different (poly)phenol amounts by ten individuals. Dose‐dependent increases in FMD at 1, 2, 4, 6, and 8 h with a peak at 4 h were observed. Sixty metabolites were quantified in plasma after cranberry consumption. Twelve (poly)phenol metabolites significantly correlated with FMD increases, including ferulic and caffeic acid sulfates, quercetin‐3‐ O ‐ß‐D‐glucuronide and a γ‐valerolactone sulfate. (Poly)phenols in cranberry juice can improve vascular function in healthy males. Abstract : Scope: Cranberries are rich in potentially bioactive (poly)phenols. The aim of this paper was to investigate whether cranberry juice intake can improve vascular function in healthy men in a dose‐ and time‐dependent manner, and to understand which of the circulating (poly)phenol metabolites correlate with vascular effects. Methods and results: A double‐blind randomized controlled crossover trial was conducted in ten healthy males. Flow‐mediated dilation (FMD), blood pressure, pulse wave velocity and augmentation index were investigated at baseline, 1, 2, 4, 6, and 8 h post‐consumption of cranberry juices containing 409, 787, 1238, 1534, and 1910 mg of total cranberry (poly)phenols (TP), and a control drink. Plasma (poly)phenol metabolites were analyzed by UPLC‐Q‐TOF MS using authentic standards. We observed dose‐dependent increases in FMD at 1, 2, 4, 6, and 8 h with a peak at 4 h and maximal effects with juice containing 1238 mg TP. A total of 60 metabolites were quantified in plasma after cranberry consumption. Twelve (poly)phenol metabolites significantly correlated with the increases in FMD, including ferulic and caffeic acid sulfates, quercetin‐3‐ O ‐ß‐D‐glucuronide and a γ‐valerolactone sulfate. Conclusion: (Poly)phenols in cranberry juice can improve vascular function in healthy males and this is linked to the presence of specific newly identified plasma metabolites.